Causal associations of hand grip strength with bone mineral density and fracture risk: A mendelian randomization study - Song, Jidong; Liu, Tun; Zhao, Jiaxin; Wang, Siyuan; Dang, Xiaoqian; Wang, Wei (Frontiers in Endocrinology, 2022)
Background Muscle strength has been shown to exert positive effects on bone health. The causal relationship between hand grip strength and osteoporosis is an important public health issue but is not fully revealed. The goal of this study was to investigate whether and to what extent hand grip strength affects bone mineral density (BMD) and fracture risk. Methods We conducted a state-of-the-art two-sample Mendelian randomization analysis. Genomewide significant (P<5×10-8) single nucleotide polymorphisms associated with hand grip strength were obtained. Summary level data of BMD and fractures at different body sites (lumbar spine, heel, forearm and femoral neck) was obtained from a large-scale osteoporosis database. The inverse variance weighted method was the primary method used for analysis, and the weighted-median, MR-Egger were utilized for sensitivity analyses. Results The results provided strong evidence that hand grip strength trait was causally and positively associated with lumbar spine BMD (β: 0.288, 95% CI: 0.079 to 0.497; P=0.007), while no causal relationship was found between hand grip strength and BMD at heel (β: -0.081, 95% CI: -0.232 to 0.070; P=0.295), forearm (β: 0.-0.101, 95% CI: -0.451 to 0.248; P=0.571) or femoral neck (β: 0.054, 95% CI: -0.171 to 0.278; P=0.639). In addition, no statistically significant effects were observed for hand grip strength on fracture risks (β: -0.004, 95% CI: -0.019 to 0.012; P=0.662). Conclusions This study showed a positive causal relationship between hand grip strength and lumbar BMD, which is the most common site of osteoporotic fracture, but did not find a causal relationship between hand grip strength and BMD of heel, forearm, or femoral neck. No statistically significant effect of hand grip strength on fracture risk was observed. This study indicates variations in the abilities of hand grip strength trait to causally influence BMD at different skeleton sites. These results should be considered in further studies and public health measures on osteoporosis prevention strategies.